Relationships between coping styles, emotional distress, and fear of COVID-19 among workers in the oil and gas industry in Malaysia during the COVID-19 pandemic - Joseph Kulip; Mohammad Saffree Jeffree; Pang, Nicholas Tze Ping; Nazmirrudin Nasirruddin (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The COVID-19 pandemic has had serious impacts on psychological health globally. However, very little is currently known regarding the link between fear of COVID-19 with psychological health and various coping styles, especially among oil and gas workers. This study aims to assess the prevalence of depression and anxiety among oil and gas workers, and subsequently examine the role of sociodemographic and occupational variables, various coping styles, and emotional distress in contributing to fear of COVID-19. A total of 299 oil and gas workers participated in this study. The DASS-21, Brief COPE, and Fear of COVID-19 (FCV-19) were used to assess the research variables. The descriptive analyses of DASS-21 indicated a prevalence of 26.8%, 33.5%, and 17.1% for depression, anxiety, and stress, respectively, among oil and gas workers. The results also indicated that all types of coping styles (problem-oriented, emotion-oriented, and dysfunctional-oriented) were significant predictors of fear of COVID-19. Sociodemographic and occupational variables and emotional distress variables were not significant predictors of fear of COVID-19. The study suggests how crucial it is for occupational mental health surveillance and prompt intervention for oil and gas workers.